2017
DOI: 10.1002/ange.201701759
|View full text |Cite
|
Sign up to set email alerts
|

Grain‐Boundary‐Free Super‐Proton Conduction of a Solution‐Processed Prussian‐Blue Nanoparticle Film

Abstract: Supportinginformation and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The first breakthrough curve of methanol and water for the MnHCC sample is shown in Figure S10; the pristine MnHCC sample adsorbed less methanol compared with the reused MnHCC after desorption. We speculate that a strong hydrogen network, including vacancy sites, was present in the MnHCC synthesized in the aqueous solution; 31 as a result, it was difficult for methanol to replace water.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The first breakthrough curve of methanol and water for the MnHCC sample is shown in Figure S10; the pristine MnHCC sample adsorbed less methanol compared with the reused MnHCC after desorption. We speculate that a strong hydrogen network, including vacancy sites, was present in the MnHCC synthesized in the aqueous solution; 31 as a result, it was difficult for methanol to replace water.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, the proton conductivity of PB-SM26 displayed a sudden increase between 80% and 95% relative humidity, resulting in a high proton conductivity comparable to that of Nafion. In previous reports, grain-boundary-free PB nanofilms exhibited nonlinear curves, 23 suggesting that the nonlinearity observed for the PB nanoparticles might be attributed to surface effects.…”
mentioning
confidence: 84%
“…[20][21][22] A study by Ono et al showed that a grain-boundary-free PB nanofilm with a self-assembled monolayer exhibits high proton conductivity (approximately 0.1 S cm À1 ). 23 However, proton conductors with bulk structures are more suitable for use in fuel cells than thin films. If PB can demonstrate such high proton conductivity in a bulk form, it can serve as a low-cost, fluorine-free electrolyte for fuel cells.…”
mentioning
confidence: 99%
“…[39] Furthermore, by controlling the valance states of the carbon-coordinated Fe ions and nitrogen-coordinated M ions, one can further vary the M/Fe stoichiometry from 1/1 to 4/3 and to 3/2 (Figure 4d-f ), among which the Turnbull's blue analogue (TBA) of M II [Fe III (CN) 6 ] 2/3 possesses the highest extent of structural defects and the richest water content. [22,71] Interestingly, the zeolitic water in cages and the ligand water in vacancy sites can form a contiguous network by hydrogen bonds, which makes it viable for the fast proton conduction via the Grotthuss mechanism (Figure 1d). Therefore, a high-rate proton battery is feasible.…”
Section: Prussian Blue Analoguesmentioning
confidence: 99%
“…Specifically, the charge of protons can be rapidly transported through the chains of water molecules via the bond vibrations of the H⋯O hydrogen bonds and H─O covalent bonds (Figure 1d), which has been discovered to be applicable to hydrous solid compounds. [22,23] This promises a superior fast-charging performance. Last but not least, protons essentially pertain to the category of nonmetal ions, which can form both ionic bonds and quasicovalent hydrogen bonds with the host frameworks, which differs from metal ions that usually bind the electrodes with ionic bonds solely.…”
Section: Introductionmentioning
confidence: 99%